Study of Morphological Characters of Pollen Grains Sweet Chestnut (Castanea sativa Mill.) by Scanning Electron Microscopy - Horčinová Sedláčková, Vladimíra; Grygorieva, Olga; Gurnenko, Ivan (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2021)
The studying of Castanea sativa Mill. pollen allows us to determine the details of morphological characteristics and described the most important parameters and pollen sculpture that can be used to identify representatives of species. The general characteristics and significant morphological traits of pollen grains of 16 genotypes Castanea sativa Mill. collected from M.M. Gryshko National Botanical Garden of Ukraine(Kyiv) were observed via a scanning electron microscope (SEM). The measurement of morphometric parameters was carried out on 50 pollen grains from each genotype using the AxioVision Rel. 4.8.2.0 program. The length of the polar axis (P) and the equatorial diameter (E) of grain, P/E ratio were measured and their variation was compared among studied genotypes. SEM investigations showed that the pollen grains of Castanea sativa are small-sized, the equatorial view is elliptic, the polar view is angular, with convex mesocolpia, more or less circular. This study showed the small differences between the genotypes in all measured factors. The average polar axis and equatorial diameter of pollen grains values varied in the interval 19.10 ±0.21–20.53 ±0.21 and 8.86 ±0.05–9.85 ±0.08, respectively. We determined the variation coefficient in the range of 3.37–8.93 %. It was noted that diversity of surface sculpturing of pollen grains in combination with shape and sizes enables to use of a complex of thin morphological signs for Castanea sativa pollen identifications.